2021
DOI: 10.1093/ndt/gfab196
|View full text |Cite
|
Sign up to set email alerts
|

Clinical triage of patients on kidney replacement therapy presenting with COVID-19: an ERACODA registry analysis

Abstract: Rationale & Objective Patients on kidney replacement therapy (KRT) are at a very high risk of COVID-19. Triage pathway for KRT patients presenting with varying severity of COVID-19 illness remains ill-defined. We studied clinical characteristics of patients at initial and subsequent hospital presentations and its impact on patient outcomes. Study Design, Setting, Participants European Renal Association COVID-19 Database (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In another study conducted by the European Renal Association COVID-19 Database, including 1423 end-stage renal disease patients with COVID-19 (HD ¼ 1017 patients/kidney transplant recipients ¼ 406 patients), the higher age, prior smoking history, higher clinical frailty score, and self-reported shortness of breath at first presentation were identified as predictors of mortality in those discharged at initial triage. 15 They also showed that among nonhospitalized patients, 10% (n ¼ 36) were readmitted to the hospital; these patients had worsening respiratory symptoms, a fall in oxygen saturation (97% vs. 90%), and high CRP between attendances (26 vs. 73 mg/l).…”
Section: Discussionmentioning
confidence: 98%
“…In another study conducted by the European Renal Association COVID-19 Database, including 1423 end-stage renal disease patients with COVID-19 (HD ¼ 1017 patients/kidney transplant recipients ¼ 406 patients), the higher age, prior smoking history, higher clinical frailty score, and self-reported shortness of breath at first presentation were identified as predictors of mortality in those discharged at initial triage. 15 They also showed that among nonhospitalized patients, 10% (n ¼ 36) were readmitted to the hospital; these patients had worsening respiratory symptoms, a fall in oxygen saturation (97% vs. 90%), and high CRP between attendances (26 vs. 73 mg/l).…”
Section: Discussionmentioning
confidence: 98%
“…We found overall mortality rates in patients receiving HD who are ambulant and not requiring admission at the time of COVID diagnosis (6%) were significantly lower than those recently reported in a large European cohort, where 28-day mortality was around 30%. 6 The majority of the study cohort was White which may contribute to the reduced mortality seen compared to other studies.…”
mentioning
confidence: 93%
“…Cumulative time on HD therapy and past medical history of diabetes mellitus, lung disease, and recent (within 30 days of positive swab) immunosuppression did not significantly differ between groups; however, a history of cardiovascular disease was more common in controls (Table 1). There was no difference seen in the overall admission rate (Figure 1a), but there was a significant delay in admission in cases compared to controls (8 [7][8][9][10][11][12][13][14][15][16][17][18] vs. 4 [2][3][4][5][6][7] days after positive swab, p = 0.03). Management through the pathway was not associated with a shorter length of hospital stay in those admitted (cases: 8 [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] days, controls: 8 [6-10], p = 0.81).…”
mentioning
confidence: 99%
See 1 more Smart Citation